PETROLEUM SLUDGE AS AN ALTERNATIVE FOR GREEN CONSTRUCTION MATERIAL - MAHADZIR, MOHAMAD LUQMAN (Universiti Teknologi PETRONAS, 2017)
Petroleum sludge is one of the major source of waste that is generated in the oil and gas industry. Petroleum sludge is categorized as a hazardous waste material based on the Resource Conservation and Recovery Act (RCRA) as the toxic materials contains hazardous composition such as hydrocarbons, heavy metals, Polycyclic Aromatic Hydrocarbon (PAH). An estimate of 50 tons of oil sludge is produced per day per 105 000 barrels per day production oil refinery. A cost-effective treatment of the petroleum sludge with a concise disposal of the hazardous material has become a major problem globally. This study discussed a suitable method of treating the petroleum sludge using stabilization and solidification method onto the petroleum sludge. Prior to the treatment of the petroleum sludge, characterization of the petroleum sludge was performed. Pozzolanic material such as cement was used to stabilize and solidify the toxic material. The cement portion of the construction block was replaced with petroleum sludge by 30%, 40% and 50% respectively. The compressive strength of each petroleum sludge construction block was done on 3days, 7 days and 21 days after curing.